Equilibrium selection with coupled populations in hawk-dove games: Theory and experiment in continuous time - Volker Benndorf; Ismael Martinez-Martinez; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Standard one- and two-population models for evolutionary games are the limit cases of a uniparametric family combining intra- and intergroup interactions. Our setup interpolates between both extremes with a coupling parameter k. For the example of the hawk-dove game, we analyze the replicator dynamics of the coupled model. We confirm the existence of a bifurcation in the dynamics of the system and identify three regions for equilibrium selection, one of which does not appear in common one- and two-population models. We also design a continuous-time experiment, exploring the dynamics and the equilibrium selection. The data largely confirm the theory.
Keywords: C62; C73; C91; C92; 330; evolutionary game theory; experiment in continuous time; hawk-dove game; replicator dynamics